2017
DOI: 10.3141/2640-03
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Vehicles

Abstract: With ongoing technological improvements and research in the field of autonomous vehicles, it is becoming evident that the technology has the potential to substantially affect the transportation sector. Although the potential benefits with respect to productivity increases, cost decreases, and safety are evident, the potential for these vehicles to negatively or positively affect the transportation infrastructure is unclear. In this study, the influence of truck loadings positioning on the long-term performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 4 publications
3
16
1
Order By: Relevance
“…This type of channelisation is also known as zero wander or less wander distribution. Channelised or less wander traffic increases the repetition of load on the narrower width of the lane (Noorvand et al, 2017) and eventually leads to pavement damage in a faster rate (Litman, 2017).…”
Section: Wheel Wander and Pavement Distressesmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of channelisation is also known as zero wander or less wander distribution. Channelised or less wander traffic increases the repetition of load on the narrower width of the lane (Noorvand et al, 2017) and eventually leads to pavement damage in a faster rate (Litman, 2017).…”
Section: Wheel Wander and Pavement Distressesmentioning
confidence: 99%
“…AASHTOWare was used in this study with proper modifications of traffic input to control vehicle positioning. The thickness for different positioning was evaluated for three lanes highway (Noorvand et al, 2017). Authors assigned a dedicated lane for more than 50% of AT volume.…”
Section: Current Knowledge On Pavement Damagementioning
confidence: 99%
See 1 more Smart Citation
“…For example, long platoons may disturb the traffic flow and make it difficult for other vehicles to merge. As for the influence on infrastructure, long platoons especially long automated truck platoons would contribute to increased wear and tear of roads due to channelized traffic and excessive concentration of wheel path regarding the lateral position [57,58], which increases the life cycle costs. e impact of the truck platoon on road infrastructure has already attracted attention.…”
Section: Future Workmentioning
confidence: 99%
“…e impact of the truck platoon on road infrastructure has already attracted attention. Noorvand et al [57] conducted a pavement performance simulation, and they suggested a dedicated lane for autonomous vehicles. Chen et al [59] estimated rutting depth and fatigue damage by finite element analysis and proposed four lateral control modes for autonomous trucks.…”
Section: Future Workmentioning
confidence: 99%